Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Eatboss Manggala - Hani Humaeriyah; Fadia Solehah; Hany Fauzyah; Shinta Zenia; Siti Almunawaroh (INDO PUBLISHING, 2026)
This study aims to analyze the influence of leadership and work discipline on employee performance at Eatboss Manggala Bandung. The study employed a quantitative approach with descriptive and verification methods. The population was all 35 employees at Eatboss Manggala Bandung, using a saturated sampling technique. Data were collected through a questionnaire structured based on indicators of leadership, work discipline, and employee performance. Data were analyzed using SPSS version 27. Data analysis techniques included validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The results showed that the instruments used were valid and reliable, and the regression model met all classical assumptions. Conceptually, leadership and work discipline play a crucial role in improving employee performance. Effective leadership provides direction and motivation, while good work discipline encourages employees to work in an orderly and responsible manner. Therefore, improving leadership quality and consistently implementing work discipline can optimally improve employee performance.